Development of the hardness mathematical model of Ti-alloyed iron for cast parts used in conditions of intensive abrasive friction - Barsuk, Andriy (Technology audit and production reserves, 2024)
The object of research is wear-resistant cast iron, intended for cast parts that work under conditions of intense abrasive friction during operation. Examples of such parts can be mixer blades of various functional purposes, the operational properties of which include stability, which depends on the hardness, determined on the HRC scale. To give such cast parts wear-resistant properties, the cast iron from which they are made is alloyed with elements that contribute to the formation of carbides of different composition: W, V, Mo, Ti, etc. The main problem that prevents the purposeful selection of materials is incomplete knowledge about the effect of chemical composition on properties, in particular, wear resistance, which prevents a justified selection criterion. Using regression analysis methods, a mathematical model was obtained, including a regression equation of the form HRC=f(C; Ceq; Ti), which relates the content of carbon, titanium and carbon equivalent in cast iron and hardness. The resulting model allows for purposeful selection of the chemical composition, which ensures a given value of HRC, on which wear resistance depends. Optimization of the chemical composition, performed according to this model, made it possible to determine that the chemical composition, which provides the maximum hardness of HRC=49, is outside the planning area: C=3.54 %, Ceq=3.95 %, Ti=3.56 %. It was established that the same value of hardness can be obtained inside the considered planning area, which has an arbitrary appearance, provided with available conditions of a passive experiment. According to the available experimental data, the values of the input variables equal to C=3.34 %, Ceq=3.727 %, Ti=0.73 % ensure obtaining hardness at the level of HRC=49. Such alternative options regarding composition and properties may indicate that the HRC=f(C; Ceq; Ti) response surface has a complex appearance that requires additional research.